Celebrity Political Party Endorsement and Voter Behaviour: A Post-election Empirical Evidence - Senanu, Bright; Amu, Prince Yao; Mensah, Hannah Ampomah (Journal of Marketing Communications (Taylor & Francis), 2023)
The study submits a piece of real-life empirical evidence on voter choice influenced by celebrity endorsement in an election other than the dominant evidence of measured intentions in the scant literature on celebrity political party endorsements and voter behaviour. It responds to calls for more research on the subject, which is motivated by country-specific political nuances and their associated voter behaviour variations that affect measures of celebrity political endorsements. Drawing on the source credibility model, the study examined the influence of celebrity endorsements on voters’ choice of political party brands in Ghana. Attractiveness, trustworthiness, and expertise were conceptualised as a tri-component construct that influenced voters’ choices of endorsed political parties at the polls. Voters’ political salience was included in the model as a moderating variable, with voters’ age and gender as control variables. Leveraging scales from extant literature, data was collected from 1463 voters right after participating in the 2020 Ghanaian general elections using purposive sampling and the intercept mode. The results indicate positive relationships between trustworthiness, attractiveness, and voters’ political brand choice. While political salience moderated the relationship between trustworthiness and voters’ choice, the control variables provided no support for their hypothesised relationships. Compelling implications and recommendations are discussed.
Research Article
Keywords: Celebrity politicalendorsements; trustworthiness; attractiveness; voter politicalsalience; voter political brandchoice; Ghana